Russian translation and validation of SarQoL® – quality of life questionnaire for patients with sarcopenia - Yu. A. Safonova; O. M. Lesnyak; I. A. Baranova; A. K. Suleimanova; E. G. Zotkin (Научно-практическая ревматология)
The aim is to carry out language adaptation and validation on the Russian sample of a special SarQoL questionnaire, designed to assess the quality of life of elderly people with sarcopenia. Material and methods. 100 patients over 65 years, mean age 74.0±6.5 years, observed on an outpatient basis were included. 50 from them had sarcopenia and 50 participants were without it. The diagnosis of sarcopenia was based on criteria developed by the European working group on sarcopenia (EWGSOP, 2010). The validation procedure was carried out in accordance with the Protocol. Results and discussion. There was a significant decrease in the overall quality of life according to SarQoL questionnaire in patients with sarcopenia compared with the control group without sarcopenia (50.65±14.23 and 75.10±14.46, respectively; p<0.001). High internal consistency of the SarQoL (Cronbach's á coefficient 0.924) was revealed. A significant positive correlation of domains with the overall SarQoL index in the range from r=0.37, p=0.0083 to r=0.92, p<0.001 was established. Moderate correlations of SarQoL with some domains SF-36 and the EQ-5D questionnaires were revealed. High internal consistency (ICC) of 0.935 (95% CI 0.91-0.96) was found. Conclusion. The Russian version of the SarQoL questionnaire is valid, consistent and reliable and can be used to assess the quality of life in older patients with sarcopenia.